Preparation of patients with low pressure lifting patients - Katarzyna Sawicka; Marek Prasał; Ewa Krzyżanowska; Robert Jan Łuczyk; Monika Trąbka; Jadwiga Daniluk (Kazimierz Wielki University, 2017)
Admission. Hypertension is one of the most common cardiovascular diseases. Treatment of hypertension in addition to standard pharmacotherapy also includes non-pharmacological treatment. Health behaviors have a significant impact on the wellbeing of patients with hypertension, control and prevent complications, so health education is essential to help patients prepare for self-control. Aim of the job. Determining the degree of preparation of patients with hypertension for self-control. Material and method. The study was conducted among 110 patients treated for hypertension using a questionnaire consisting of a questionnaire consisting of a questionnaire and 23 questions. Results. Based on the study, it was found that the majority of patients with hypertension had a mediocre knowledge of the principles of self-monitoring and that sociodemographic factors had no effect on the degree of self-monitoring of hypertension. Only the education of the subjects and the duration of the disease significantly affect the preparation of patients for self-control of the disease.